Factors Affecting Consumer’s Intention to Use Electric Vehicles: Mediating Role of Awareness and Knowledge - Shantanu Gupta; Rohit Bansal; Neha Bankoti; Sanjay Kumar Kar; Saroj Kumar Mishra; Palvinder Kaur; Sidharth Harichandan (Journal of Advanced Transportation)
This paper explores the role of environmental consequences, perceived barriers, policy interventions, public opinions, and knowledge and awareness in using electric vehicles (EVs). We collected 506 responses about their intention to use the EVs to develop our hypothesis. This study uses knowledge and awareness of the EVs as mediating variables towards adopting the EVs and consumers’ residences as moderating variables. It also introduces several control variables in this proposed research model to measure the effect on the intention to use the EVs. In this research study, we test the importance-performance map analysis and check Cohen’s f2 to identify a better output. The measurement and structural equation modelling results show that the environmental consequences are a stronger predictor of intention and policy interventions. The findings suggest that government policies can also have an attractive position in the EV segment. In addition, knowledge and awareness mediate the adoption of the EVs. Perceived barriers do not influence consumers to use an EV in India. We test the moderating role of residence with our construct and find a partial moderation role with policy intervention and public opinion. We introduce three self-created constructs, i.e., intention to use, knowledge, and public opinion. Public opinion for the EVs supports consumers’ intention to use, and knowledge also plays a significant role in using EVs. These newly added constructs will be essential to manufacturers and policymakers while promoting EVs. Also, environmental consequences and policy interventions emerge as significant factors of user behaviour. The paper highlights the critical predictors of consumers’ intention to use the EVs. Thus, it helps society, policymakers, and managers formulate and implement schemes to boost EV purchasing.